Monitoring carbon monoxide emission in the air using wireless application / Ahmad Noor Zaini Mohammad Zaibi - Mohammad Zaibi, Ahmad Noor Zaini (2012)
Concerning due to very high load of carbon monoxide emission in the air, this study is to monitor the CO emission load via wireless application. Earlier research done showed that the Potential Health Hazards of Air Pollution especially carbon monoxide (CO) give various unhealthy effects. At low concentrations, it can fatigue in healthy people and chest pain in people with heart disease. At higher concentrations, it can impaired vision and coordination; headaches; dizziness; confusion; nausea also can cause flu-like symptoms that clear up after leaving home and the worst effect is fatal at very high concentrations. In this system will be focus on collecting data from TGS 800 sensors and stored in PIC16F887, then using (GSM) modem the data sent as a Short Messaging System (SMS) alert to the subscriber's mobile phone.